Who receives oral nutritional supplements in nursing homes? Results from the nutritionDay project - Streicher, Melanie; Themessl-Huber, Michael; Schindler, Karin; Sieber, Cornel; Hiesmayr, Michael; Volkert, Dorothee (Clinical Nutrition, 2017)
Background & aims: Oral nutritional supplements (ONS) can be helpful for nursing home (NH) residents to prevent or treat malnutrition. Presently little is known about the use of ONS in NHs and the factors associated with its use. Thus, the aim of this analysis was to describe the use of ONS in NHs participating in the nutritionDay project and to determine characteristics of NH residents receiving ONS.Methods: Data from nutritionDay (nD), a cross-sectional multicenter study with standardized questionnaires on resident and NH level were analyzed. NH residents participating between 2007 and 2014 aged 65 years or older were included. Unit characteristics (2 variables), general residents' characteristics (18), residents' nutritional status (3) and residents' nutrition (4) were of interest as potential predictors of the use of ONS (no vs yes). Univariate binary logistic regression (LR) analyses were performed for all variables, and significant predictors (p < 0.05) subsequently included in a multivariate analysis (backwards LR).Results: 13.9% of 23,689 NH residents received ONS. Univariate analysis identified all variables as predictors. After multivariate analysis 19 variables remained in the model (Nagelkerke's R-2 = 0.319). Odds ratios (OR [95% Confidence Interval]) of receiving ONS were highest in residents receiving supplementary parenteral nutrition (29.05 [14.85-56.81]; however only 1.1% of all participants) and fortified diet (11.91 [8.52-16.64]; 5.7%). The odds ratio of receiving ONS was 3.26 ([2.86-3.71]; 18.3%) for residents being classified as at risk of malnutrition and 4.56 ([3.86-5.40]; 10.0%) for malnourished residents according to NH staff. Low BMI and weight loss in the last year increased the odds of receiving ONS by 2.34 ([1.93 -2.84]; 16.0%) and 1.38 ([1.23-1.54]; 32.8%), respectively. Furthermore, increasing age, cognitive and functional impairment, low food intake on nD, neurological disease and cancer were associated with an increased likelihood of the use of ONS. In NH units with a nutritional expert (67.1%) and units performing a nutritional assessment at least once a month (71.6%), the odds of receiving ONS were also significantly increased (1.89 [1.71-2.10] and 1.17 [1.06-1.29]).Conclusion: In NHs who participated in the nutritionDay, ONS are used for residents with poor nutritional and functional status and often in combination with other nutritional interventions. Riture studies need to clarify the role of NH staff in the prescription and distribution of ONS and focus on the reasons for and adequacy of the use of ONS in NHs. (C) 2016 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: ONS; Nursing home; Nutritional support; Malnutrition; Food intake